Implications for COVID-19 vaccine uptake: A systematic review. Issue 3 (March 2023) - Adu, Peter; Popoola, Tosin; Medvedev, Oleg N.; Collings, Sunny; Mbinta, James; Aspin, Clive; Simpson, Colin R.
Abstract: Background: Globally, increasing coronavirus disease (COVID-19) vaccination coverage remains a major public health concern in the face of high rates of COVID-19 hesitancy among the general population. We must understand the impact of the determinants of COVID-19 vaccine uptake when designing national vaccination programmes. We aimed to synthesise nationwide evidence regarding COVID-19 infodemics and the demographic, psychological, and social predictors of COVID-19 vaccination uptake. Methods: We systematically searched seven databases between July 2021 and March 2022 to retrieve relevant articles published since COVID-19 was first reported on 31 December 2019 in Wuhan, China. Of the 12, 502 peer-reviewed articles retrieved from the databases, 57 met the selection criteria and were included in this systematic review. We explored COVID-19 vaccine uptake determinants before and after the first COVID-19 vaccine roll-out by the Food and Drug Authority (FDA). Results: Increased COVID-19 vaccine uptake rates were associated with decreased hesitancy. Concerns about COVID-19 vaccine safety, negative side effects, rapid development of the COVID-19 vaccine, and uncertainty about vaccine effectiveness were associated with reluctance to be vaccinated. After the US FDA approval of COVID-19 vaccines, phobia of medical procedures such as vaccine injection and inadequate information about vaccines were the main determinants of COVID-19 vaccine hesitancy. Conclusion: Addressing effectiveness and safety concerns regarding COVID-19 vaccines, as well as providing adequate information about vaccines and the impacts of pandemics, should be considered before implementation of any vaccination programme. Reassuring people about the safety of medical vaccination and using alternative procedures such as needle-free vaccination may help further increase vaccination uptake.